Compassion, Acts of Contrition, and Forgiveness in Middle and Late Life - Krause, Neal M. (Pastoral psychology, 2016)
The purpose of this study is to assess social and psychological factors that have not been examined frequently in studies on forgiving others. A latent variable model is developed that contains the following core relationships: (1) people who attend worship services more often will receive more informal spiritual support from fellow church members; (2) individuals who get more spiritual support will be more compassionate; (3) people who are more compassionate will be less likely to require transgressors to perform acts of contrition; and (4) individuals who do not require transgressors to perform acts of contrition will find it easier to forgive. Data from a nationwide survey of middle-aged and older adults provides support for each of these relationships.